Bad Attitude(s) on Trial : Pornography, Feminism, and the Butler Decision - Cossman, Brenda, 1960- (Book collections on Project MUSE., 1997)
"Bad Attitude/s on Trial is a critical analysis of pornography in the context of contemporary Canada. The notion that pornography both reflects sexual domination and 'victimizes' women has recently found expression in law in the landmark Canadian Supreme Court decision of R. v. Butler (1992). Many feminists embrace this new law as progressive, but in the post-Butler years, straight, mainstream pornography is still flourishing, while sexual representations that challenge conventional notions of sexuality, such as those centring on gay and lesbian sex and s/m sex, are the focus of censorship. It is the censorship of sexual others that the authors critique from a legal, cultural, gay, and philosophical standpoint." "Bad Attitude/s on Trial provides a new debate on pornography and feminism. It will be of particular interest to students of both women's and gay and lesbian issues, but will also be relevant for scholars of law, political science, and philosophy, as well as for anyone interested in a different, provocative view of the Butler decision."--Jacket